Multidrug Resistant Brain Abscess Due to Acinetobacter baumannii Ventriculitis Cleared by Intraventricular and Intravenous Tigecycline Therapy: A Case Report and Review of Literature - Long, Wenyong; Yuan, Jian; Liu, Jingping; Liu, Jinfang; Wu, Ming; Chen, Xin; Peng, Gang; Wu, Changwu; Zhang, Chi; Wang, Xiangyu; Zhao, Wei; Liu, Qing (Frontiers in Neurology, 2018)
OBJECTIVE Ventricular infection from multidrug-resistant (MDR) Acinetobacter baumannii (A. baumannii) is one of the severe complications of craniotomy. However, the availability of effective therapeutic options for these infections are limited. Thus, this report aimed to describe the efficacy of abscess clearance by intraventricular and intravenous tigecycline therapy in managing patients with multidrug-resistant A. baumannii ventriculitis after neurosurgery. Moreover, the current literature on the use of tigecycline therapy for these life-threatening infections is reviewed and summarized, and a treatment regimen based on the available data was proposed. METHODS A patient with multidrug-resistant A. baumannii ventriculitis was admitted in our hospital and was provided with a detailed therapeutic schedule. Tigecycline treatments for multidrug-resistant A. baumannii ventriculitis that were reported in the literature were also reviewed and summarized. RESULTS The patient in our hospital underwent abscess clearance on a ventriculoscope and was subsequently subjected to multi-route tigecycline therapy 14 days after the start of the continuous ventricular irrigation (CVI) tigecycline and 3 days after the intraventricular (IVT) tigecycline. The signs of ventriculitis disappeared, and the Acinetobacter cerebrospinal fluid (CSF) load steadily decreased until CSF sterilization. Literature review identified seven cases of ventricular infection from multidrug-resistant A. baumannii treated with tigecycline. In the eight cases, all patients were male adults (>18 years), with a mean age of 46.1 (range: 22–75) years. Meningitis/ventriculitis was secondary to neurosurgery procedures for the management of various central nervous system diseases in all cases. A good clinical outcome was achieved in all eight patients with multidrug-resistant A. baumannii meningitis/ventriculitis treated with CVI and/or IVT tigecycline, and any relevant complications were not observed. CONCLUSIONS CVI and IVT tigecycline and IVT colistin could be considered as the first-line therapy in patients with ventricular infections from MDR/extreme drug-resistant A. baumannii. However, more studies should be conducted to confirm our observation.